'Rounding' for better patient care: An evaluation of an improvement intervention implementation. Issue 2 (4th March 2014) - Walker, Kim; Duff, Jed; Fitzgerald, Katherine
<x xml:space="preserve">Abstract</x> 'Rounding' is reported to be an effective intervention to enhance patient‐centred care; nurses make frequent calls on their patients to ensure their needs are met and reassure them they are the focus of their care. In our hospital, two clinical units implemented rounding as improvement projects and asked the research unit to evaluate the effectiveness of implementation. A qualitative descriptive study using focus groups and in‐depth interviews revealed that although the idea of rounding was well intended, it was not as effectively implemented as it might have been. Consequently, lessons have been learnt about the difficulties of changing clinician behaviour and will inform a new attempt at implementation.